Application of Extreme Programming in the Design and Development of a Web-Based Inventory Information System at the Kerinci District Communication and Information Office - Eastyanda Putra Kesuma; Ulfa Khaira; Muhammad Razi A (Faktor Exacta, 2025)
The management of inventory at the Department of Communication and Informatics in Kerinci Regency faced challenges due to centralized processes and the limitations of the existing desktop-based application, the Regional Management Information System, which did not meet user needs. To address this, a web-based inventory management system was developed to enhance operational efficiency, data accuracy, and real-time accessibility. The system was built using the Extreme Programming method over two iterations. The first iteration focused on inventory data management, item categorization, and asset history tracking, while the second iteration introduced features for reporting asset conditions, data validation, and recap reports. The development process included planning, design, coding, and testing phases. User acceptance testing and performance testing were conducted to ensure system quality and user satisfaction. The results demonstrated that the system functioned effectively, met user requirements, and supported efficient inventory management. This system is expected to improve transparency, operational efficiency, and public services at the Department of Communication and Informatics in Kerinci Regency.